Trends in income inequality: comparing the United States and Portugal - Cantante, F. (2017)
This article presents a comparative analysis of the United States and Portugal in terms of economic inequality from the early twentieth century to the present decade. We use different measures of inequality from several statistical sources. The article revolves around three complementary points. The first is a synchronic and diachronic analysis of economic inequalities in Portugal and the United States, the second is the issue of redistribution of income and the final analysis addresses the evolution of top incomes in both countries.